Glaucoma Control Strategies in Sub-Saharan Africa: A Review of the Clinical and Health Economic Evidence. (2nd November 2018) - Smith, Andrew F.; Negretti, Guy; Mascaro, Aaron; Bokre, Desta; Baker, Helen; Dhalla, Kazim; Murdoch, Ian E.
ABSTRACT: Purpose : A review of the effectiveness, costs, and cost-effectiveness of detection and treatment strategies for glaucoma control in Sub-Saharan Africa (SSA) was conducted. Methods : Detailed searches were performed using the Ovid Medline, Ovid Embase, The Cochrane Library, Web of Science, Scopus, and LILACS databases up to September 2016. The key Medical Subject Heading search terms used included glaucoma, diagnosis, treatment, effectiveness, costs, cost-effectiveness, and Sub-Saharan Africa . Effectiveness was measured as the proportion of study participants with an intra-ocular pressure less than or equal to 22 mmHg. Results : A total of 5658 records were examined with 48 papers identified. The sensitivity and specificity of portable instruments or smartphone technologies to detect glaucomatous changes ranged from 58.3% to 93.8% and from 82.4% to 96.8%, respectively. The overall effect size for various glaucoma interventions was: 0.39 (95% confidence interval (CI) 0.27–0.54, I 2 = 64.85, p = 0.036) for laser trabeculoplasty; 0.56 (95% CI 0.23–0.84, I 2 = 85.74, p = 0.001) for drainage implant devices; 0.66 (95% CI 0.61–0.71, I 2 = 0.00, p = 0.402) for medical management; and 0.73 (95% CI 0.65–0.80, I 2 = 93.25, p = 0.000) for all other non-drainage tube surgical interventions, including trabeculectomy surgery and the use of anti-metabolites. The mean annual cost of anti-glaucoma drugs across SSA was USD 394, with a mean direct non-medication cost per year of USD 54, and a mean surgical cost per year of USD 283. Conclusions : While effective glaucoma control interventions exist, their widespread use and diffusion across SSA remain challenging principally due to low per capita income levels and high glaucoma treatment costs.